2016
DOI: 10.1038/srep35670
|View full text |Cite
|
Sign up to set email alerts
|

Core Amino Acid Residues in the Morphology-Regulating Protein, Mms6, for Intracellular Magnetite Biomineralization

Abstract: Living organisms produce finely tuned biomineral architectures with the aid of biomineral-associated proteins. The functional amino acid residues in these proteins have been previously identified using in vitro and in silico experimentation in different biomineralization systems. However, the investigation in living organisms is limited owing to the difficulty in establishing appropriate genetic techniques. Mms6 protein, isolated from the surface of magnetite crystals synthesized in magnetotactic bacteria, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…The Mms6-MIC sequence contains seven negatively charged residues in total but the three residues Asp12, Glu13 and Asp19 showed the most significant changes during iron titration. Similar to the in vivo analysis, a single mutation on Asp12 and Glue13 showed a significant effect on magnetite crystal shape and size in MTB ( Yamagishi et al, 2016 ). One can thus assume that the other negative residues have some effect on ion binding and contribute to the negatively charged environment.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The Mms6-MIC sequence contains seven negatively charged residues in total but the three residues Asp12, Glu13 and Asp19 showed the most significant changes during iron titration. Similar to the in vivo analysis, a single mutation on Asp12 and Glue13 showed a significant effect on magnetite crystal shape and size in MTB ( Yamagishi et al, 2016 ). One can thus assume that the other negative residues have some effect on ion binding and contribute to the negatively charged environment.…”
Section: Discussionsupporting
confidence: 61%
“…In summary, our results shed light on the residues that are involved in magnetite formation and their abilities to interact with specific ions. According to the literature, Mms6 is involved in magnetite nucleation, with deletion of mms6 or only its C-terminus causing changes in the size and shape of magnetite particles ( Tanaka et al, 2011 ; Kashyap et al, 2014 ; Yamagishi et al, 2016 ). In this study, in vitro iron co-precipitation by the Mms6-MIC had a minor effect on magnetite size and shape, which indicates that the major role of the protein is not realized during crystal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As AgNPs with unique morphologies were also observed after long reaction times in this study, the difference in reaction kinetics seems to be a key factor for the formation of different sizes and morphologies of AgNPs, as discussed in a previous study on AuNP synthesis regulation [29][30][31]. In addition, further investigation of the interaction between peptides and specific crystal facets should be performed to elucidate the morphological regulation, because various biological molecules bound to a specific crystal surface are suggested to contribute to morphological regulation in the biomineralization process [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 62%
“…Mms6 is the most abundant and most studied MAP and, using mms6-knockout mutants, has been shown to be involved in magnetite formation in the magnetosome (Raschdorf et al, 2017). The deletion or mutation of mms6 caused defects in the size and shape of magnetite particles (Amemiya et al, 2007;Tanaka et al, 2011;Yamagishi et al, 2016). In vitro studies also showed that Mms6 affects magnetite particle size and shape during iron precipitation and that the 22 C-terminal residues are essential for function (Kashyap et al, 2014;Rawlings et al, 2016;Yamagishi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%